PERBANDINGAN EFEKTIFITAS MEDIA E-BOOKLET DAN VIDEO ANIMASI TERHADAP PENGETAHUAN DAN SIKAP TERKAIT ANEMIA REMAJA PUTRI DI SMA KOSGORO KOTA BOGOR - Angelita Afina Arif Putri (2022)
Nutritional needs will increase during adolescent as a support of physical and psychological development and growth. Insufficient intake of nutrients that occurs in adolescents will cause nutritional problems, one of which is anemia. The purpose of this study was to analyze the comparison the effectiveness of e-booklets and animation videos on knowledge and attitudes related to anemia in adolescent girls. This research is a quasi-experimental with nonequivalent control group design. The sample of this research are students from class X and XI at SMA Kosgoro Bogor City, which were divided into 3 groups there are e-booklets group, animation video, and control groups who were not given nutrition education with a total of 71 students. The results showed that there were differences in knowledge and attitudes related to anemia between before and after being given nutrition education using e-booklets and animation videos with a p-value 0,000. The effectiveness variable showed results, there was no difference in the effectiveness of nutrition education between e-booklets media and animation video media on knowledge and attitudes related to anemia in adolescent girls with a p-value of 0.704 knowledge and a p-value of 0,996 attitudes. Nutrition education with e-booklets and animation video has an effect on increasing the knowledge and attitudes of adolescent girls related to anemia, both of these media have their respective advantages as effective nutrition education to increase adolescent knowledge and attitudes related to anemia.